2007
DOI: 10.1088/0957-4484/18/38/385102
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of highly stable folic acid conjugated magnetite nanoparticles for targeting cancer cells

Abstract: A new approach towards the design of folic acid conjugated magnetic nanoparticles for enhancing their site specific intracellular uptake against a folate receptor overexpressing cancer cells is reported. Magnetite nanoparticles were prepared by coprecipitation from an Fe3+ and Fe2+ solution followed by surface modification with 2-carboxyethyl phosphonic acid to form carboxyl group terminated nanoparticles. Then folic acid and fluorescein isothiocyanate (FITC) were conjugated with carboxylic acid functionaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
113
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(120 citation statements)
references
References 35 publications
6
113
1
Order By: Relevance
“…We bound folic acid to the surface of the UCNs in an attempt to aid their targeting to folate receptors that are overexpressed in B16-F0 melanoma cells 24 , and the PEG component enhanced the circulatory lifetime of the UCNs so they had a greater chance of reaching the targeted tumor sites. Indeed, studies have shown that nanoparticles surface modified with folic acid and PEG preferentially localize in targeted tumor tissues compared to other main organs in the body 25 .…”
Section: In Vivo Pdtmentioning
confidence: 99%
“…We bound folic acid to the surface of the UCNs in an attempt to aid their targeting to folate receptors that are overexpressed in B16-F0 melanoma cells 24 , and the PEG component enhanced the circulatory lifetime of the UCNs so they had a greater chance of reaching the targeted tumor sites. Indeed, studies have shown that nanoparticles surface modified with folic acid and PEG preferentially localize in targeted tumor tissues compared to other main organs in the body 25 .…”
Section: In Vivo Pdtmentioning
confidence: 99%
“…Before reaching the target site, NPs are easily phagocytized by the reticuloendothelial system and accumulated in reticuloendothelial system-rich nontargeted organs such as liver and spleen, leading to serious side effects and lower drug concentration in the diseased organs. [12][13][14] Therefore, it is necessary to conjugate specific targeting molecules (specific of ligands, such as monoclonal antibodies) at the surface of NPs to achieve active targeting therapy by binding with specific cell surface molecules. Commonly used ligands include specific surfactant agents, folate, transferrin proteins, and polypeptides.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, peak in 1583 cm -1 could be assigned to C=O stretching. Peaks in 2926 and 2860 cm -1 could be assigned to symmetric and asymmetric C-H (Lu et al 2012) and peak in 3381 cm -1 corresponds to O-H bonding of either adsorbed water or EG (Ahmad et al 2011;Mohapatra et al 2007;Singh et al 2011). Peaks in 879, 1044, and 1376 cm -1 could be, respectively, assigned to C-C, C-O-C stretching, and C-O-H deformation vibrations.…”
Section: Surface Modificationmentioning
confidence: 99%